Mekanisme Dan Metode Perhitungan Produk Pegadaian Syariah Dalam Konsep Hukum Bisnis Syariah - Suryani, Ade Irma; Zakir, Muhammad (Journal of Legal Sustainability, 2024)
The aim of this research is to explain the mechanism of sharia pawnshops and how to calculate sharia pawnshop products. The method used in this research uses descriptive research with a qualitative approach. The data collected is in the form of regulations, mechanisms and products from Sharia Pawnshops which are obtained based on documentation from literature related to Sharia pawnshops. A literature study was carried out, namely by analyzing the problem formulation using secondary data that was available on the pawnshop website and several documented literature. The research results explain that overall, the mechanisms and calculation methods in sharia pawnshop products are designed to provide financial solutions that are ethical, fair, and in accordance with Islamic principles, which provide an alternative for people who want to avoid usury transactions. In terms of the mechanism and method of calculation, sharia pawnshops make profits by entrusting services, not by interest as is practiced in conventional pawnshops. For each product, sharia pawnshops also take advantage by using different administration fees for each product. These administrative costs have a tendency to make costs at sharia pawnshops quite high, but are balanced with a high level of transparency. Finally, each financial institution will be selected based on the needs, level of trust, and fees charged by the customer. In practice, sharia pawnshops are still in the process of improving in terms of services, mechanisms and other related matters. And for every scholar who is involved in the world of sharia finance, he should be able to improve the sharia financial system by continuing to develop various methods and ijtihad ideas so that the benefits of sharia finance can be felt by the whole community, especially in the use of sharia pawnshop services